Pengaruh Job Insecurity terhadap Turnover Intention melalui Organizational Commitment pada Karyawan Perbankan di Surabaya - Erlina Nadhiroh; Budiono Budiono (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This research were conducted to study the effect of job insecurity to turnover intention through organizational commitment in bank employees in the city of Surabaya. This approach uses in this research is a quantitative approach, while accidental sampling is a sampling technique used by means 81 respondent in the city of Surabaya.Data were collected based on interviews and questionnaires distributed to employees, then carried out using the SmartPLS 3.2.9 software. This study reveals that job insecurity has a positive and significant effect on turnover intention, job insecurity has a negative and insignificant effect on organizational commitment, organizational commitment has a negative and significant effect on turnover intention, and it can be concluded that organizational commitment does not mediate the effect of job insecurity on turnover intention of employees. The answer to this research is that the direct effect of job insecurity is greater than the indirect effect on turnover intention. This research implies that the company is expected to be able to maintain security for employees by creating a harmonious atmosphere in the work environment and involving employees in company activities to maintain their commitment to the company. To increase turnover intention, companies can implement policies that do not harm the company and its employees, for example bypaying attention to working hours so as not to cause burnout due the working hours that are too high.